People Powering Progress: How Human Resource Influences Your Company’s Digitalization and Sustainable Growth - Esses, Diana (Cognitive Sustainability, 2024)
The digital world holds many opportunities and challenges for us. These changes affect all the basic pillars of sustainability, including the economy, society, and the environment. They primarily affect companies, specifically theirproductivity and profitability, so it is not an exaggeration to say that nowadays, we can consider the digital maturity of companies as one of the driving forces of the economy. The research aims to prioritise the digital competence of theworkforce among the indicators of digital maturity, which, based on my hypotheses, has the greatest impact on the profitability of businesses. Another main research goal is to map the cognitive sustainability-related activities of humanresources employed by companies and then present the relationship between digital maturity and sustainability through human resources. In this study, the digital maturity of companies was assessed, especially the role of human digital skills in productivity based on Maslow’s business pyramid and a SWOT analysis. I compared the cognitive sustainability-related activities of human resources and examined how this affects the company’s effectiveness.